Population of Potential Rattan in Bukit Tiban Protection Forest, Batam, Indonesia - Rizki Ary Fambayun; Titi Kalima (Jurnal Penelitian Kehutanan Wallacea, 2020)
Rattan is one of the promising non-timber forest products which grow widely in Indonesia. The occurrence of rattan species, especially the commercial species, is threatened due to illegal over-exploitation. The study has been done in the Bukit Tiban Protection Forest (BTPF) to investigate the occurrence of rattan species and observe the characteristic of morphology properties and their utilization. In this study, a descriptive exploration method was applied and we performed an interview with local people in the field regarding the utilization. Morphological characteristics observed including habitus, leaves (such as color, leaflets, leaf arrangement, knee, ocrea, and climbing organ/cirrus/flagellum), and fruit. The identification key, illustrations, as well as the diagnostic character of each species were presented. Ten species of rattans were found in the BTPF, namely Calamussp.1 (Daemonorops verticillaris(Griff.) Martius), Calamussp.2 (Calamus rugosusBeccari), rotan sabut (Daemonorops sabutBeccari), rotan buah kecil (Daemonorops didymophyllaBeccari), Plectocomiasp. (Plectocomia elongate Martius ex Blume), rotan bukit (Daemonorops sepalBeccari), rotan dahan (Korthalsia rostrataBlume), Calamussp.5 (Calamus spectatissimusFurtado), Calamussp. (Daemonorops longipes(Griff.) Martius), and Calamus sp.6 (Calamus tanakadateiFurtado). Those ten species of rattan are potentially used for handicrafts, basketry, and ropes. Only five of ten species of rattan have been used commercially.